2007
DOI: 10.1128/jvi.01732-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CD46 Binding Sites within the Adenovirus Serotype 35 Fiber Knob

Abstract: Species B human adenoviruses (Ads) are often associated with fatal illnesses in immunocompromised individuals. Recently, species B Ads, most of which use the ubiquitously expressed complement regulatory protein CD46 as a primary attachment receptor, have gained interest for use as gene therapy vectors. In this study, we focused on species B Ad serotype 35 (Ad35), whose trimeric fiber knob domain binds to three CD46 molecules with a K D (equilibrium dissociation constant) of 15.5 nM. To study the Ad35 knob-CD46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
86
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 31 publications
5
86
1
Order By: Relevance
“…Fiber trimerization is crucial for binding of Ad35 fiber proteins to human CD46. 31,40 As shown in the upper panel of Figure 2, we detected a band of 110 kDa corresponding to the trimerized fibers in all the lanes for the AdF35 vectors, including the fiber-modified AdF35 vectors. In addition, the mutant Ad35 fibers containing the foreign peptides were detected at a higher position, compared with the wild-type Ad35 fibers, under a denaturing condition (Figure 2, lower panel) due to the incorporation of 13 (RGD peptide) and 16 amino acids (FLAG peptide) into the fiber knob.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…Fiber trimerization is crucial for binding of Ad35 fiber proteins to human CD46. 31,40 As shown in the upper panel of Figure 2, we detected a band of 110 kDa corresponding to the trimerized fibers in all the lanes for the AdF35 vectors, including the fiber-modified AdF35 vectors. In addition, the mutant Ad35 fibers containing the foreign peptides were detected at a higher position, compared with the wild-type Ad35 fibers, under a denaturing condition (Figure 2, lower panel) due to the incorporation of 13 (RGD peptide) and 16 amino acids (FLAG peptide) into the fiber knob.…”
mentioning
confidence: 68%
“…Recent studies have revealed the structure of species B Ad fiber knobs, the mode of interaction with CD46 and several amino acids crucial for CD46 binding in the fiber knob, [28][29][30][31] and that the FG, HI and IJ loops are involved in the association with CD46. [31][32][33] In particular, Phe242 in the FG loop, Arg279 and Ser282 in the HI loop, and Glu302 in the IJ loop are crucial for attachment to CD46 (note that the numbers of amino-acid residues are those of the Ad35 fiber knob).…”
mentioning
confidence: 99%
See 3 more Smart Citations